Reduced beta 2-microglobulin mRNA levels in transgenic mice expressing a designed hammerhead ribozyme. - Larsson, S (1994)
We have generated three artificial hammerhead ribozymes, denoted 'Rz-b', 'Rz-c' and 'Rz-d', with different specificities for exon II of the mouse beta-2-microglobulin (beta 2M) mRNA. In this study we tested for ribozyme mediated reduction of beta 2M mRNA in a cell line and in transgenic mice. Transfections of either of the Rz-b, Rz-c or Rz-d plasmids into a mouse cell-line (NIH/3T3) revealed reductions of beta 2M mRNA substrate in each case. Ribozyme expression in individual transfected clones was accompanied with an up to 80% reduction of beta 2M mRNA levels. Rz-c was selected for a transgenic study. Seven Rz-c transgenic founder animals were identified from which three ribozyme expressing families were established and analysed. Expression of the ribozyme transgene was tested for and detected in lung, kidney and spleen. Expression was accompanied with reduction of the beta 2M mRNA levels of heterozygous (Rz+/-) animals compared to non-transgenic litter mates. The effect was most pronounced in lung with more than 90% beta 2M mRNA reduction in individual mice. In summary, expression of our ribozymes in a cell free system, in a cell-line and in transgenic mice were all accompanied with reductions of beta 2M mRNA levels.